Patah Titie dalam Kewarisan - Zul Azimi; Desra Fanzudiah (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2021)
The problem in this study is how the practice of inheritance "patah titie" in Tangse District Pidie, how it impacts, and how the review of Islamic law on the practice. The method used in this study is qualitative method that uses observation, interview and documentation as data collection techniques. The results showed that the practice of "patah titie" that developed in tangse society often caused prejudice and inequality among the community. The impact that often arises as a result of the practice of "patah titie" is strife, strain until the breakup of family relationships. While the review of Islamic law shows that the practice of "patah titie" that applies among tangse people is basically not forbidden in Islam, because in Islamic law "patah titie", known as hijab andmahjub, it's just that people do not understand about it so as to cause problems. The author concludes that the practice of "patah titie" is in no way in violation of the rules of Islamic inheritance, because the problems and gaps that occur among the community is the result of the negligence of the community itself in understanding and studying the actual inheritance law recommended in Islam. The author's advice should give a small part of the inheritance to the heirs of the "patah titie" to protect and protect the family from disputes and disputes.